Simbolisme Budaya Jawa dalam Arsitektur Kompleks Masjid Kudus Sebagai Strategi Dakwah Islam di Jawa Abad Ke-15 - Rehan Ismail Adi Nasahudin (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to examine the manifestations of Javanese cultural symbolism embedded in the architecture of the Kudus Mosque Complex and to analyze its function as a strategic medium for Islamic propagation (da'wah) during the fifteenth and sixteenth centuries. Employing a historical research method with a qualitative approach, the study follows the stages of heuristics, source criticism, interpretation, and historiography. The data were collected through an extensive review of scholarly literature, including academic journals, books, and architectural documentation related to the Islamization of Java and the architectural heritage of the Kudus Mosque. The findings reveal that the Kudus Mosque Complex represents a remarkable example of cultural acculturation among Javanese, Hindu-Buddhist, and Islamic traditions, as reflected in its architectural elements, including the Hindu temple-like Kudus Minaret, the gapura bentar and paduraksa gateways, the three-tiered (tumpang tiga) roof, the soko guru (main structural pillars), the Buddhist-inspired ablution fountains, and the spatial organization of the mosque complex based on the mandala concept. These architectural features function not merely as structural components but also as symbolic expressions deliberately employed by Sunan Kudus as an effective medium for communicating Islamic teachings. Through a culturally accommodative approach that respected and incorporated local traditions, Islam was accepted peacefully by the Javanese community without eroding their pre-existing cultural identity. This da'wah strategy significantly contributed to the expansion of Islam in Kudus and fostered the emergence of distinctive religious traditions that reflect the harmonious integration of Javanese cultural values and Islamic principles. Accordingly, the Javanese cultural symbolism embodied in the architecture of the Kudus Mosque Complex stands as compelling evidence of the success of an inclusive model of Islamic propagation founded upon cultural acculturation, religious tolerance, and profound respect for local wisdom.